Hubungan Pengetahuan Terhadap Sikap Remaja Putri dalam Mengelola Dismenorea di MTS Assalam Manado - Rakija Haris; Sri Atikah Mokodongan; Meinita Wulansari (Universitas Pahlawan Tuanku Tambusai, 2026)
Adolescence is a time of rapid change and development both in terms of physical, psychological, and intellectual. In women, the changes and developments that occur are marked by the onset of menstruation. The purpose of this study was to see the influence of knowledge on the attitude of adolescent girls in managing dysmenorrhea at MTs Assalam Manado. The population in this study were 28 female adolescents in grade XI. This study was conducted in January 2025. The type of research uses a quantitative correlational method with a cross-sectional approach. This research was conducted at MTs Assalam Manado. The sampling technique used Total Sampling. Sample collection using questionnaires, then the data is processed using the Chi-square statistical test with a significance level of p = (a < 0.000). The results of the Chi-square statistical test with a significance level of p = (a < 0.000). This means that there is an influence of knowledge on the attitude of adolescent girls in managing dysmenorrhea at MTs Assalam Manado. The conclusion of this study is that there is an influence of knowledge on the attitude of adolescent girls in managing dysmenorrhea at MTs Assalam Manado. Suggestions The results of this study are basic knowledge for students and for further developments in the field of midwifery